Peran Guru PAI dalam Membentuk Karakter Religius Terhadap Siswa MAN 3 Banyuwangi Tahun Ajaran 2023-2024 - Irawan, Deni; Syahid, Mar; Fitria, Mulajimatul (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) STIB Banyuwangi, 2024)
An important part of education is the formation of religious character, which aims to build students' personalities with Islamic values ​​such as honesty, responsibility, discipline, and tolerance. Islamic Religious Education teachers have a strategic role as educators, mentors, and role models for students to internalize religious principles in our daily lives. The research method used by the researcher is a qualitative approach. Data obtained by the researcher through observation, in-depth interviews, and document analysis. The results of this study indicate that the role of Islamic Religious Education (PAI) teachers at MAN 3 Banyuwangi is very crucial in the formation of students' religious character. Islamic Religious Education teachers deliver religious material in an interesting and interactive way, and become role models who inspire students to apply religious values ​​in their daily lives. The support and guidance provided by Islamic Religious Education teachers help students overcome challenges in the development of their religious character. However, environmental factors, both in the family and social circles, also influence the success of this process. Synergy between education in schools, family support, and the social environment is needed to achieve optimal results in the formation of students' religious character